Blood pressure and cardiovascular diseases in Chinese adults with type 2 diabetes: A prospective cohort study - Fiona Bragg; Jim Halsey; Yu Guo; Hua Zhang; Ling Yang; Xiaohui Sun; Pei Pei; Yiping Chen; Huaidong Du; Canqing Yu; Robert Clarke; Jun Lv; et al. (Elsevier, 2021)
Background: Controversy persists about the relationship of blood pressure with cardiovascular diseases (CVD) in diabetes and associated disease burden. We assessed these associations among Chinese adults with type 2 diabetes (T2D). Methods: In 2004-08, the China Kadoorie Biobank recruited >512,000 adults aged 30-79 years from 10 localities across China, including 26,315 with T2D (based on self-report or plasma glucose measurement) but no prior CVD, followed-up for ~9 years. Cox regression yielded adjusted HR for major CVD and all-cause mortality associated with 10 mmHg higher usual (longer-term average) SBP. Attributable fractions were estimated to assess cardiovascular mortality burden due to uncontrolled hypertension (SBP ≥130 mmHg or DBP ≥80 mmHg). Findings: Overall, 75.7% of participants had self-reported (24.8%) or screen-detected (50.9%) (SBP ≥130 mmHg or DBP ≥80 mmHg) hypertension. Among individuals with self-reported hypertension, 82.3% were treated, of whom 9.3% achieved control. There were positive log-linear associations of blood pressure with CVD, with no evidence of a threshold down to ~120 mmHg for usual SBP. Each 10 mmHg higher usual SBP was associated with HR of 1.28 (95% CI 1.25-1.30), 1.18 (1.15-1.21), 1.17 (1.15-1.19) and 1.45 (1.38-1.52) for cardiovascular death (n=1807), major coronary event (n=1190), ischaemic stroke (n=4362) and intracerebral haemorrhage (n=469), respectively. There was an apparent J-shaped association with all-cause mortality (n=4503). In this diabetes population, uncontrolled hypertension accounted for 39% of cardiovascular deaths. Interpretation: Uncontrolled hypertension is common in Chinese adults with T2D, resulting in substantial excess risks of CVD. Improved hypertension management could avoid a large number of cardiovascular-related deaths. Funding: Kadoorie Foundation, Wellcome Trust, MRC, BHF, CR-UK, MoST, NNSF.